Contraception and Conception After Bariatric Surgery. Issue 5 (November 2017) - Menke, Marie N.; King, Wendy C.; White, Gretchen E.; Gosman, Gabriella G.; Courcoulas, Anita P.; Dakin, Gregory F.; Flum, David R.; Orcutt, Molly J.; Pomp, Alfons; Pories, Walter J.; Purnell, Jonathan Q.; Steffen, Kristine J.; et al.
Abstract : OBJECTIVE: To examine contraceptive practices and conception rates after bariatric surgery. METHODS: The Longitudinal Assessment of Bariatric Surgery-2 is a multicenter, prospective cohort study of adults undergoing first-time bariatric surgery as part of routine clinical care at 10 U.S. hospitals. Recruitment occurred between 2005 and 2009. Participants completed preoperative and annual postsurgical assessments for up to 7 years until January 2015. This report was restricted to women 18–44 years old with no history of menopause, hysterectomy, or estrogen and progesterone therapy. Primary outcomes were self-reported contraceptive practices, overall conception rate, and early (less than 18 months) postsurgical conception. Contraceptive practice (no intercourse, protected intercourse, unprotected intercourse, or tried to conceive) was classified based on the preceding year. Conception rates were determined from self-reported pregnancies. RESULTS: Of 740 eligible women, 710 (95.9%) completed follow-up assessment(s). Median (interquartile range) preoperative age was 34 (30–39) years. In the first postsurgical year, 12.7% (95% CI 9.4–16.0) of women had no intercourse, 40.5% (95% CI 35.6–45.4) had protected intercourse only, 41.5% (95% CI 36.4–46.6) had unprotected intercourse while not trying to conceive, and 4.3% (95% CI 2.4–6.3) tried to conceive. The prevalence of the first three groups did not significantly differ across the 7 years of follow-up ( P for all >.05); however, more women tried to conceive in the second year (13.1%, 95% CI 9.3–17.0; P <.001). The conception rate was 53.8 (95% CI 40.0–71.1) per 1, 000 woman-years across follow-up (median [interquartile range] 6.5 [5.9–7.0] years); 42.3 (95% CI 30.2–57.6) per 1, 000 woman-years in the 18 months after surgery. Age (adjusted relative risk 0.41 [95% CI 0.19–0.89] per 10 years, P =.03), being married or living as married (adjusted relative risk 4.76 [95% CI 2.02–11.21], P <.001), and rating future pregnancy as important preoperatively (adjusted relative risk 8.50 [95% CI 2.92–24.75], P <.001) were associated with early conception. CONCLUSIONS: Postsurgical contraceptive use and conception rates do not reflect recommendations for an 18-month delay in conception after bariatric surgery. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT00465829. Abstract : Contraceptive use and conception rates after bariatric surgery do not reflect recommendations for an 18-month delay in conception.